Structural and functional predictors of atrial appendages thrombi organization in persistent non-valvular atrial fibrillation patients. - Kalashnykova, O. S. (Морфологія / Morphologia / Morfologìâ, 2013)
Goal: to study predictors of atrial appendages thrombi organization in persistent non-valvular atrial fibrillation patients.Materials and methods: a total of 133 consecutive patients with non-valvular atrial fibrillation, who underwent transoesophageal echocardiography before electrical cardioversion, were included in the study. Results: in 40 (37,6%) patients thrombus were detected in left atrial appendage and in 26 (65,0%) patients they were organized. In 10 (7,5%) patients thrombus were detected in right atrial appendage and in 7 (70,0%) patients they were organized. In 63 (47,4%) patients thrombi were found in both atrial appendages and in 25 (39,7%) patients they were organized. Hemodynamic and morphological predictors of left atrial appendage thrombus in non-valvular atrial fibrillation patients were not found. Thrombus organization in right atrial appendage was assotiated with increased left atrial and right atrial indexed area and volume in systole and diastole, increased thickness of rear wall of left ventricle.Conclusions: predictors of right atrial appendage thrombi organization in non-valvular atrial fibrillation patients are increased left atrial andright atrial indexed area and volume in systole and diastole, increased thickness of rear wall of left ventricle.